Government and Politics in South Asia - Baxter, Craig; Malik, Yogendra K.; Kennedy, Charles H. 1951- and Oberst, Robert C. (Lahore Pak Book Corporation, 1993)
A systematically comparative introduction to the political frameworks of the major nations of South Asia: India, Pakistan, Bangladesh, Sri Lanka, and Nepal.
Include Maps, Tables and Index
Keywords: South Asia -- Political science -- South Asia -- Political